Predictors of repeat transarterial chemoembolization in the treatment of hepatocellular carcinoma - White, Jared A (HPB (Oxford), 2014)
OBJECTIVES: Repeat transarterial chemoembolization (TACE) is a common intervention performed for hepatocellular carcinoma (HCC). The aim of this study was to identify predictors of the need for repeat TACE. METHODS: Between 2008 and 2012, data on patient and tumour variables were collected for 262 patients treated with a first TACE procedure for HCC. The decision to perform repeat TACE procedures was made at the completion of the first TACE or after follow-up imaging demonstrated the subtotal treatment of HCC tumours. RESULTS: Repeat TACE was performed in 67 of 262 (25.6%) patients. Necrosis of HCC, measured after the first TACE, was lower in patients who subsequently received repeat TACE (P = 0.042). On multivariable analysis, total tumour diameter of >5 cm [odds ratio (OR) 2.76, 95% confidence interval (CI) 1.45–5.25; P = 0.002] and increasing age (OR 1.04/year, 95% CI 1.00–1.07; P = 0.030) were predictive of the need for repeat TACE. Measures of liver function and TACE approach (selective versus non-selective) were not predictive of repeat TACE. Median survival did not differ significantly between patients who did (median survival: 21.1 months) and did not (median survival: 26.1 months) receive a repeat TACE procedure (P = 0.574). CONCLUSIONS: The requirement for repeat TACE is associated with older age, increased HCC tumour burden and subtotal TACE-induced HCC necrosis. Importantly, repeat TACE was not associated with reduced survival.